All‐Day Operating Quaternary Blend Organic Photovoltaics. (25th February 2019) - Nam, Minwoo; Noh, Hye Yeon; Cho, Junhee; Park, Yongkook; Shin, Sang‐Chul; Kim, Jung‐A; Kim, Jehan; Lee, Hyun Hwi; Shim, Jae Won; Ko, Doo‐Hyun
Abstract: The unique properties of organic photovoltaics (OPVs) offer great promise in emerging applications such as wearable electronics or the Internet of Things. For their successful utilization, OPV operation should be designed for versatile irradiation circumstances in addition to solar light since they should be capable of providing electric power when there is no sunlight or when they operate indoors. Here, a quaternary OPV (Q‐OPV) as a semitransparent, colorful energy platform that operates efficiently under both solar and artificial light irradiation is demonstrated. The experimentally optimized Q‐OPV shows a broadened spectral response and improved charge transport process with suppressed recombination, thereby providing high output powers that are sufficient to autonomously operate low‐power electronic devices. In addition, the Q‐OPV benefits from improved morphological stability with a reduced driving force for grain growth by the increased entropy in the quaternary blend system. The important features of the Q‐OPV platform such as semitransparency, high tolerance to film thickness, and color codability, while pursuing the improved performance and thermal durability, further open new opportunities as an all‐day (24/7/365) power generator in broad practical applications. Abstract : Quaternary blend organic photovoltaics (Q‐OPVs) exhibit efficient operation under diverse irradiation conditions and improved thermal durability with suppressed morphological evolution during operation. The unique properties of the Q‐OPVs such as semitransparency, high film thickness tolerance, and color codability expand their applicability to emerging energy systems, which operate autonomously by any incident light all day, even when there is no sunlight.